2013
DOI: 10.3201/eid1908.130121
|View full text |Cite
|
Sign up to set email alerts
|

The New Global Health

Abstract: Global health reflects the realities of globalization, including worldwide dissemination of infectious and noninfectious public health risks. Global health architecture is complex and better coordination is needed between multiple organizations. Three overlapping themes determine global health action and prioritization: development, security, and public health. These themes play out against a background of demographic change, socioeconomic development, and urbanization. Infectious diseases remain critical fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…This result was expected due to high number of old farmers participating in beef farming in communal areas of Chief Albert Luthuli municipality. Although the educational levels of the respondents were low, it should be taken into consideration that the older generation grew up in the apartheid era and had limited access to formal education (De Cock et al, 2013) and hence, it is possible that the reason for these high number of uneducated beef cattle farmers in Chief Albert Luthuli municipality was caused by apartheid era regime; during which in most cases, they were not allowed to attend schools but rather were drafted to work in farms and their responsibilities were to herd livestock from morning until the evening. In agreement with the results of the present study, Mngomezulu (2010) reported that 54.2% of farmers did not attend school in Eastern Cape, South Africa.…”
Section: Demographics and Socio-economic Aspects Of The Respondentsmentioning
confidence: 99%
“…This result was expected due to high number of old farmers participating in beef farming in communal areas of Chief Albert Luthuli municipality. Although the educational levels of the respondents were low, it should be taken into consideration that the older generation grew up in the apartheid era and had limited access to formal education (De Cock et al, 2013) and hence, it is possible that the reason for these high number of uneducated beef cattle farmers in Chief Albert Luthuli municipality was caused by apartheid era regime; during which in most cases, they were not allowed to attend schools but rather were drafted to work in farms and their responsibilities were to herd livestock from morning until the evening. In agreement with the results of the present study, Mngomezulu (2010) reported that 54.2% of farmers did not attend school in Eastern Cape, South Africa.…”
Section: Demographics and Socio-economic Aspects Of The Respondentsmentioning
confidence: 99%
“…Rather, non-communicable diseases, injuries, and mental health are becoming the major cause of global illness and death (De Cock, 2011;De Cock et al, 2013). This global health trend underscores the increasing importance to public health in a host country of providing immigrants with access to preventive health care services.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars (De Cock, 2011;De Cock et al, 2013) with the Centers for Disease Control and Prevention (CDC) have acknowledged the interlocking relationship between global health and domestic public health and have asserted that the collective efforts of all countries are required to meet the objectives of health equity and universal access and coverage as priorities in an interdependent world. Prior to 1996 when PRWORA was enacted, U.S. policy was similar to that of other liberal, industrialized democracies such as Canada and Australia, granting permanent residents the same eligibility for health benefits as citizens (Aleinikoff & Klusmeyer, 2002;Fix & Laglagaron, 2002).…”
Section: Literature Review Welfare Reform and Older Adult Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Cock and colleagues note, “It is difficult to explain why investment in separating human drinking water from human feces, the basis of the nineteenth century public health revolution in Europe and North America, has not been a higher political or development priority in resource-poor settings” ( 5 , p. 1195). If we acknowledge our interconnectedness through social, economic, and political dimensions, that there exist severe shortcomings in health equity both within and between countries, and that these challenges require cooperation beyond the traditional donor-recipient model, then perhaps we will come to terms with why deaths from malaria, TB, or diarrheal diseases implicate all of us, and matter ( 5 ). Engagement in global health is not just a humanitarian endeavor; it is a priority for our collective well-being.…”
mentioning
confidence: 99%